Developing Research Skills in Criminology Students Through Interdisciplinary Approaches - Gerona, Jayson; Marimon, Christian; Ostos, Omesirg; Pontillas, Rey Anthony (Journal of Interdisciplinary Perspectives, 2025)
This study examines the effect of interdisciplinary approaches on the development of research skills among criminology students at St. Francis Xavier College. Recognizing the critical need for research competence in criminology, this study examines how integrating insights from various disciplines, such as law, psychology, and sociology, enhances students' abilities to formulate research questions, design methodologies, and analyze data. Utilizing a quantitative, descriptive-correlational research design, data were collected from 245 criminology students at St. Francis Xavier College through a structured survey questionnaire. Findings indicate that interdisciplinary approaches, particularly curriculum integration, effective teaching strategies, and student engagement, significantly influence the development of research skills. Results show very high levels of both interdisciplinary approaches and research skills, with strong positive correlations between the two variables. Notably, student engagement was found to have the most substantial impact on research attitude and confidence. The study underscores the importance of adopting interdisciplinary frameworks in criminology education to foster critical thinking and evidence-based practice. Recommendations include enhancing curriculum design to reflect interdisciplinary connections, employing interactive teaching strategies, and promoting student engagement through collaborative research activities. This research contributes to the understanding of how interdisciplinary learning can prepare criminology students for effective research and professional practice, aligning with the goals of quality education and sustainable development.